Investigation on hydrogenation performance of Mg17Al12 by adding Y - Hua Ning; Guang Wei; Jianhong Chen; Zhipeng Meng; Zhiwen Wang; Zhiqiang Lan; Xiantun Huang; Junyu Chen; Peilin Qing; Haizhen Liu; Wenzheng Zhou; Jin Guo (Scientific Reports, 2024)
Abstract The mechanism of Y on H/H2 adsorption performance of Mg17Al12 were studied by the density functional theory. We obtained that for the Y-adsorbed systems, Y tended to occupy on the bridge site between adjacent Mg atoms. For the Y-substituted surfaces, Y atoms inclined to replace Mg atoms on the surfaces. We found that hydrogen (H/H2) absorption on the Mg17Al12(110) systems were improved by adding Y, the order of adsorption energy was as follows: clean Mg17Al12(110) > the Y-substituted surfaces > the Y-adsorbed surfaces. In addition, H2 molecules could dissociate on the Y-containing systems without barrier energy. Electronic properties showed that for H2 adsorption, the s states of atomic H mainly hybridized with the d states of Y. The formations of the Y-H bonds and the interactions between Y and H atoms could expound the mechanism for the promoted hydrogenation performance of the Y-containing surfaces.